Zioła i ich znaczenie dla człowieka - Kapusta, Franciszek (Herbs and Their Importance for the Man, 2007)
Herbs constitute a large group of plants characterised by biologically active ingredients, which have impact on live organisms. Based on their impact they are divided into: medicinal, spice, honeygiving, cosmetical, stimulants, herbal tea, aphrodisiacs and others. The puipose of planting herbs is to obtain specific chemical compounds, generally called active ingredients: oils, alcaloids, glicasoids, tannins, vitamins. Herbs have been useful for human beings for ages and their role in human life has been changing with tendency to discover their new characteristics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 7-19